Spatial relationship between lightning narrow bipolar events and parent thunderstorms as revealed by phased array radar. Issue 3 (13th February 2013) - Wu, Ting; Takayanagi, Yuji; Yoshida, Satoru; Funaki, Tsuyoshi; Ushio, Tomoo; Kawasaki, Zen
Abstract [1] Phased array radar with unprecedented high temporal and spatial resolution is used for the first time to analyze structures of thunderstorms producing lightning narrow bipolar events (NBEs). Locations of NBEs generally correspond well with the deepest convection, but in some thunderstorms extending higher than 15 km, positive NBEs cluster around, rather than right at the center of the core of deep convection. Negative NBEs are generally higher than positive NBEs and are usually produced at the cloud top of the thunderstorm. Positive NBEs, on the other hand, are always located well inside the thundercloud. It seems that negative NBEs can only be produced in very vigorous thunderstorms with cloud tops higher than about 14 km. Numerous thunderstorms with lower height produce few negative NBEs, indicating a height threshold for NBE production. On the basis of these findings, it becomes very convenient and accurate to monitor severe thunderstorms with negative NBEs.